REVITALISASI PENGGUNAAN OBAT GENERIK - Yunarto, Nanang (University of Muhammadiyah Malang, 2011)
The government through the Ministry of Health is very serious about revitalizing the use of generic drugs by issuing a policy that stipulated in the Regulation of the Minister of Health No. HK. 02.02/Menkes/068/1/2010 about duty to use generic drugs in government health care facilities. To maximize the use of generic drugs, it is very important to improve understanding and trust of society that generic drugs have the quality, safety and effectiveness are similar to branded drugs. Besides that, there is a lot of research and the study of generic drugs will increase the knowledge, so that health professionals, especially doctors do not hesitate to prescribe generic drugs. Quality used as a basis of reference to establish the truth of the eficacy and safety. For availability of certain products can be demonstrated in vitro. Studies of drug dissolution gave the same indication with drug bioavailability. Ideally, in vitro drug dissolution correlates bioavailability in vivo. From the research results of dissolution test generic drugs Amoxiciline 500 mg tablets, Isosorbit Dinitrat 5 mg tablets and Omeprazole capsules compared to branded drugs show no less generic drugs than branded drugs, dissolution test results even better generic drugs